Bodies in Conflict: Understanding Women’s Experiences of Polycystic Ovarian Syndrome - Chowdhuri, Samadrita (Atlantis)

(untitled) (Mount Saint Vincent University, 2026)
Polycystic Ovarian Syndrome (PCOS) is a complex medical condition that impacts women’s bodies and identities, especially in relation to gendered expectations of health and femininity. Drawing on feminist and social constructionist frameworks, this study uses ideas of “doing gender” and “undoing gender,” in connection with the concept of medicalization, to investigate the relationship between self-perception, medical authority, and gender norms. This qualitative study examined the embodied experiences of Indian and Indo-Canadian women living with PCOS in Edmonton, Canada, using semi-structured interviews, focus group discussions, and body mapping as the primary methods of data collection. According to the findings, women establish a hierarchy of symptoms, giving external symptoms like acne and hirsutism precedence over issues about fertility. This hierarchy is a reflection of internalized ideas of feminine appearance and also a rejection of feminine functionality focused on reproductivity. The women’s choices of treatment, especially with regard to hormonal contraceptives, reflect a negotiation between defying and adhering to sociocultural and biological standards of womanhood. This study challenges conventional medicalized discourses on PCOS by emphasizing women’s narratives, and advances a more comprehensive understanding of gender, health, and embodiment. It emphasizes the necessity of more patient-centered approaches to recognize and validate opportunities for healing that are not based on predetermined and essentialist notions of health and femininity.